ANALISIS PENERAPAN MODEL PROJECT BASED LEARNING DENGAN PENDEKATAN DIFERENSIASI PADA PEMBELAJARAN IPAS KELAS V DI SD NEGERI TANDANG 01 - Selvi Tirta Kurniawati; Sindhu Marta Atasya; Shindika Bachtiar Tri Permana; Mira Azizah; Danik Setyorini (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
ABSTRACT This research was motivated by the learning conditions in class V of SD Negeri Tandang 01, where a uniform learning pattern was still applied without considering differences in students’ learning styles, readiness, and interests. This study aims to analyze the implementation of the Project Based Learning (PjBL) model with a differentiated approach in IPAS learning for class V during the 2025/2026 academic year. The research employed a descriptive qualitative method through the stages of planning, implementation, and evaluation. In the planning stage, teachers conducted cognitive and non-cognitive diagnostic assessments to identify students’ learning styles. During the implementation stage, differentiation was applied to content and process aspects through six PjBL syntax stages: determining fundamental questions, project planning, scheduling, monitoring progress, testing results, and evaluating experiences. The material on types of waste and waste management was presented through PPT, videos, concrete media, and interactive games to accommodate visual, auditory, and kinesthetic learning styles. The diagnostic assessment results showed diverse student learning styles, so learning activities were designed using varied media and activities that suited these characteristics. Observations during the learning process indicated increased participation in group discussions, teamwork, confidence in expressing opinions, and engagement in completing waste management projects. The results showed that the implementation of PjBL with a differentiated approach had a positive impact on students’ understanding, motivation, and learning outcomes. Students were also able to produce project products aligned with learning objectives while developing critical thinking, creativity, collaboration, and communication skills as 21st-century competencies in an inclusive and student-centered learning environment. ABSTRAK Penelitian ini dilatarbelakangi oleh kondisi pembelajaran di kelas V SD Negeri Tandang 01 yang masih menggunakan pola seragam tanpa mempertimbangkan perbedaan gaya belajar, kesiapan, dan minat peserta didik. Penelitian ini bertujuan menganalisis penerapan model Project Based Learning (PjBL) dengan pendekatan berdiferensiasi pada pembelajaran IPAS kelas V tahun ajaran 2025/2026. Metode yang digunakan adalah kualitatif deskriptif melalui tahapan perencanaan, pelaksanaan, dan evaluasi. Pada tahap perencanaan, guru melakukan asesmen diagnostik kognitif dan non-kognitif untuk memetakan gaya belajar peserta didik. Pada tahap pelaksanaan, diferensiasi diterapkan pada aspek konten dan proses melalui enam sintaks PjBL, yaitu penentuan pertanyaan mendasar, perencanaan proyek, penyusunan jadwal, monitoring kemajuan, pengujian hasil, dan evaluasi pengalaman. Materi jenis sampah dan pengelolaannya disajikan melalui PPT, video, media konkret, dan game interaktif untuk mengakomodasi gaya belajar visual, auditori, dan kinestetik. Hasil asesmen diagnostik menunjukkan keberagaman gaya belajar peserta didik sehingga pembelajaran dirancang dengan variasi media dan aktivitas yang sesuai. Observasi selama pembelajaran menunjukkan peningkatan keaktifan diskusi, kerja sama, keberanian menyampaikan pendapat, serta keterlibatan dalam penyelesaian proyek pengelolaan sampah. Hasil penelitian menunjukkan bahwa implementasi PjBL dengan pendekatan berdiferensiasi berdampak positif terhadap pemahaman, motivasi, dan hasil belajar peserta didik. Peserta didik mampu menghasilkan produk proyek sesuai tujuan pembelajaran serta mengembangkan kemampuan berpikir kritis, kreativitas, kolaborasi, dan komunikasi sebagai kompetensi abad ke-21 dalam suasana belajar yang inklusif dan berpusat pada peserta didik.